PENGARUH ASPEK SOSIAL EKONOMI MASYARAKAT TERHADAP BANGKITAN PERGERAKAN ZONA KECAMATAN DI KOTA PALU - Ismadarni, Ismadarni (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
Population growth increases the need for housing, facilities / infrastructure and transportation. Theexpansion of the city that is not accompanied by the provision of infrastructure could result inproblems, one of them is the transportation problem. This study aims to determine the pattern of trafficmovement and socioeconomic factors that influence the trip generation in the district zones in Palu.Primary Survey conducted by delivering questionnaires to 1449 families residing in the four districtzones namely North Palu, East Palu, West Palu, and South Palu. The results of the questionnaires were tabulated to determine the amount and pattern of trip which were chosen as the independent and the dependent variable, and then analyzed through SPSS-16. Multiple linear regression equation was used to determine the factors that influence the trip generation. The analysis showed that there are three patterns of trip that occurs from each zone district in the city of Palu, i.e. Intra-zone, ekstra-zone, and Internal-External. Socioeconomic factors that influence significantly the trip generation districtzones of North Palu (Ypu), East Palu (Ypt), West Palu, (Ypb) , and South Palu, (Yps) are the number of family members (X1), the number of two-wheeler ownership (X2) and the amount of income (X5).Keyword:Â  Trip generation, Socio-economic aspect